Contrasting Patterns of Genetic Diversity in European Mammals in the Context of Glacial Refugia - Oxala García-Rodríguez; Emilie A. Hardouin; Debbi Pedreschi; Martin B. Richards; Richard Stafford; Jeremy B. Searle; John R. Stewart (Diversity, 2024)
Phylogeographic studies have been conducted on many different mammal species in order to track their recent demographic histories. The climatic fluctuations associated with the Last Glacial Maximum (LGM) appear to have had a profound influence on the geographic patterning of genetic diversity in mammals. However, most phylogenetic studies have focused on single species. Few have used a holistic approach covering multiple taxa to explore common patterns. Here, we conducted meta-analyses of mitochondrial DNA control region sequences, identifying haplotype diversity and private allelic richness patterns in a geographic context. Four general patterns emerged among European mammals: an east–west decline in variation, a Western-Central belt of the highest diversity, southern richness, and homogeneity with no geographic pattern. These patterns likely reflect the refugial origins of modern populations. The east–west variation decline suggests species with eastern LGM refugia; the Western-Central belt of the highest diversity may harbor taxa with cryptic northern refugia, while southern richness may correspond to traditional southern refugia. Species with homogeneity and no geographic pattern may have been panmictic without a specific refugium or may reflect the occurrence of both southern and cryptic northern refugia. Surprisingly, the “no pattern” phenomenon is seldom discussed and may frequently have been discounted. Our study emphasizes the importance of considering multiple taxa, providing valuable insights into the responses of European mammals to past climatic changes.